Fourier-Domain Optical Coherence Tomographic Assessment of Changes in the Schlemm’s Canal of Nonglaucomatous Subjects After Keratoplasty - Zhao, Yujin; Li, Yue; Hong, Jiaxu; Le, Qihua; Xu, Jianjiang (Frontiers in Physiology, 2021)
Purpose: To evaluate the impact of keratoplasty on the in-vivo anatomical structures of Schlemm’s canal (SC) in non-glaucomatous subjects using Fourier-domain optical coherence tomography (FD-OCT). Methods: 66 non-glaucomatous eyes that underwent keratoplasties were enrolled in this prospective, comparative observational study. SC imaging was performed using FD-OCT before and after surgery in the nasal and temporal quadrants. Patient demographics, SC parameters [CSA: cross-sectional area (CSA), SC meridional diameter of Schlemm’s canal (MSC), sagittal diameter of Schlemm’s canal (SSC), circumference (CCF)], and the correlations between variation of SC parameters and intraocular pressure (IOP) were analyzed. Results: The mean age of all subjects was (40.27 ± 18.97) years. Among all cases, nasal, temporal and the mean MSC significantly decreased on the first day after surgery, then increased at one week (p = 0.04, 0.017 and 0.01, respectively). Temporal CSA (tCSA), temporal MSC (tMSC) and temporal circumference (tCCF) after PK (p = 0.017, 0.020, 0.018), nasal MSC (nMSC) after DALK (p = 0.025) decreased significantly on the first day. The shift of mean IOP was significantly correlated with the changes of tMSC (r = 0.341, p = 0.003) and CCF (r = 0.207, p = 0.048). Conclusions: SC had significant in vivo morphological changes in the early period after keratoplasty in non-glaucomatous eyes, accompanied with IOP elevation. Early intervention might be necessary to prevent secondary glaucoma early after keratoplasty.